Resident Endoscopy Experience Correlates Poorly with Performance on a Virtual Reality Simulator - Oberoi, Kurun Partap S.; Scott, Michael T.; Schwartzman, Jacob; Mahajan, Jasmine; Patel, Nell Maloney; Alvarez-Downing, Melissa M.; Merchant, Aziz M.; Kunac, Anastasia (The Surgery Journal, 2022)
Background Endoscopy training has become increasingly emphasized during general surgery residency as reflected by introduction of the Fundamentals of Endoscopic Surgery (FES) examination, which includes testing of skills on virtual reality (VR) simulators. Although studies exist to assess the ability of the simulator to differentiate between novices and experienced endoscopists, it is not well understood how simulators can differentiate skills among resident cohort.Objective To assess the utility of the VR simulator, we evaluated the correlation between resident endoscopy experience and performance on two VR simulator colonoscopy modules on the GI-BRONCH Mentor (Simbionix Ltd, Airport City, Israel).Methods Postgraduate years 2 to 5 residents completed “easy” and “difficult” VR colonoscopies, and performance metrics were recorded from October 2017 to February 2018 at Rutgers' two general surgery residency programs. Resident endoscopy experience was obtained through Accreditation Council for Graduate Medical Education case logs. Correlations between resident endoscopy experience and VR colonoscopy performance metrics were assessed using Spearman's rho (ρ) correlation statistic and bivariate logistic regression.Results Fifty-five residents out of 65 (84.6%) eligible participants completed the study. There were limited correlations found between resident endoscopy experience and FES performance metrics and no correlations were found between resident endoscopy experience and binary metrics of colonoscopy—ability to complete colonoscopy, ability to retroflex, and withdrawal time of less than 6 minutes.Conclusion The VR simulator may have a limited ability to discriminate between experience levels among resident cohort. Future studies are needed to further understand how well the VR simulator metrics correlate with resident endoscopy experience.
Keywords: GI Mentor; colonoscopy; surgical; simulation; endoscopy; residency training